Baseline characteristics and patterns of care in testicular cancer patients: first data from the Swiss Austrian German Testicular Cancer Cohort Study (SAG TCCS): This article was corrected and republished online on August 29, 2018. Please see Correction ‒ August 29, 2018. (Swiss Medical Weekly, 2018)
BACKGROUND The majority of germ cell tumour (GCT) patients can be cured by orchiectomy followed by active surveillance or subsequent systemic and/or local treatments. There are various guidelines for a structured follow-up including radiographic and clinical examinations. OBJECTIVE The Swiss Austrian German Testicular Cancer Cohort Study (SAG TCCS) prospectively evaluates follow-up, indicator of relapse and late toxicities. This is a descriptive analysis; we present baseline characteristics and treatment strategies for the first 299 patients with primary GCT or relapsed GCT after completion of treatment. RESULTS Of the patients included in this study, 192 (64.2%) had seminoma and 107 (35.8%) non-seminoma. Mean age was 41 years (standard deviation [SD] 11.7) for seminoma and 31 (SD 9.3) years for non-seminoma patients. Median tumour size was 3.5 cm (interquartile range 2.5‒5.0 and 2.3‒4.5 in seminoma and non-seminoma, respectively) in both histological groups. Among seminoma patients, 81 (42.2%) had primary tumours >4cm; 154 (80.2%) seminoma patients had stage I, 26 (13.5%) stage II and 12 (6.3%) stage III disease. Fifty-seven (53.3%) non-seminoma tumours were stage I, 29 (27.1%) stage II and 21 (19.6%) stage III. Marker-positive disease was present in 58 (30.2%) seminoma patients and 78 (72.9%) non-seminoma patients. Of 154 stage I seminoma patients, 89 (57.8%) chose active surveillance and 65 (42.2%) adjuvant chemotherapy. Twenty-six (45.6%) stage I non-seminoma patients had high-risk disease; 23 of these were treated with adjuvant chemotherapy and 3 chose active surveillance. Among the 30 (52.6%) low risk stage I patients, all opted for active surveillance. Twelve (46.2%) stage II seminoma patients had radiotherapy, 14 (53.8%) were treated with three to four cycles of chemotherapy. All stage III seminoma patients, and all stage II and III non-seminoma patients were treated with three to four cycles of chemotherapy. Treatment decisions were made at the respective centre. Eleven patients did not receive therapy that conformed with guidelines. CONCLUSION It is important to enrol GCT patients in prospective studies in general, but also in follow-up studies to assess baseline characteristics, oncological outcome, and long-term toxicity and to validate the performance of follow-up schedules. This is the first time that the distribution of disease, detailed baseline characteristics and the respective treatment of men with GCT is collected in a prospective manner in German speaking countries (Switzerland, Austria and Germany) and therefore patterns of care have been evaluated. SAG TCCS results will inform on future modifications of surveillance schedules and follow-up procedures. ​ Trial registration number: NCT02229916 (Clinicaltrials.gov)